RIPASA vs Modified Alvarado Scoring System for Diagnosis of Appendicitis - Timilsina, Bhusan Raj; Shah, Rajiv; KC, Sudeep Raj; Upadhyay, Hari Prasad; Lamsal, Sunita; Belbase, Narayan; Kumar, Sujit (Journal of College of Medical Sciences-Nepal, 2018)
INTRODUCTION: Acute appendicitis is the most common surgical condition presented to the emergency department. Clinical scoring systems such as the Alvarado and modified Alvarado scoring system were developed with the goal of reducing the negative appendectomy rate to 5%–10%. In the other hand the Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA) scoring system was established in 2008 specifically for Asian population. The aim of this study was to compare the modified Alvarado with the RIPASA scoring system in the Nepalese population. METHODS: This study included 125 patients who had undergone appendectomies from March of 2017 to January 2018. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), diagnostic accuracy, predicted negative appendectomy and receiver operating characteristic (ROC) curve of the modified Alvarado and RIPASA scoring systems were derived using SPSS statistical software. RESULTS: A total of 125 patients were included in this study according to our criteria. The cut-off threshold point of the modified Alvarado score was set at 7.0, which yielded a sensitivity of 68.64% and a specificity of 28.57%. The PPV was 95% and the NPV was 5.12%. The cut-off threshold point of the RIPASA score was set at 7.5, which yielded 88.13% sensitivity and 28.57% specificity. The PPV was 95.41% and the NPV was 12.5%. CONCLUSION: Based on the results of this study, the RIPASA score is a simple scoring system with better sensitivity and specificity similar to the modified Alvarado scoring system. KEYWORDS: Acute appendicitis, Modified Alvarado Score, RIPASA score.